2005
DOI: 10.1354/vp.42-4-446
|View full text |Cite
|
Sign up to set email alerts
|

“Gas and Fat Embolic Syndrome” Involving a Mass Stranding of Beaked Whales (Family Ziphiidae) Exposed to Anthropogenic Sonar Signals

Abstract: A study of the lesions of beaked whales (BWs) in a recent mass stranding in the Canary Islands following naval exercises provides a possible explanation of the relationship between anthropogenic, acoustic (sonar) activities and the stranding and death of marine mammals. Fourteen BWs were stranded in the Canary Islands close to the site of an international naval exercise (Neo-Tapon 2002) held on 24 September 2002. Strandings began about 4 hours after the onset of midfrequency sonar activity. Eight Cuvier's BWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
267
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(304 citation statements)
references
References 45 publications
18
267
0
6
Order By: Relevance
“…These findings require that we reopen the discussion as to whether marine mammals are susceptible to DCS. The data we present here add credence to findings and hypotheses on the subject of susceptibility to and manifestation of DCS in bycaught and stranded marine mammals (Fernandez et al, 2005;Jepson et al, 2005;Moore et al, 2009). The data add further weight to the suggestion that marine mammals may experience supersaturation at levels that may result in asymptomatic or symptomatic inert gas bubbles when diving repetitively, acquired when lung collapse is incomplete (Hooker et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These findings require that we reopen the discussion as to whether marine mammals are susceptible to DCS. The data we present here add credence to findings and hypotheses on the subject of susceptibility to and manifestation of DCS in bycaught and stranded marine mammals (Fernandez et al, 2005;Jepson et al, 2005;Moore et al, 2009). The data add further weight to the suggestion that marine mammals may experience supersaturation at levels that may result in asymptomatic or symptomatic inert gas bubbles when diving repetitively, acquired when lung collapse is incomplete (Hooker et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…These data established the pathobiological basis for a hypothesis (Cox et al, 2006) that beaked whales are acutely (Fernandez et al, 2005), and other odontocetes are perhaps chronically (Jepson et al, 2005;Moore and Early, 2004), at risk of DCS.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…In an old animal experimental study, gas bubble emboli were observed in the renal artery and vein [20]. In another study, air emboli in the kidney veins were observed microscopically in a specimen taken from a stranded beaked whale that showed DCI-like lesions, similar to those in humans and laboratory animals [21]. In the current case, the exact cause of AKI could not be ascertained histologically because kidney biopsy was not performed due to the improvement of renal function soon after the diuretic phase.…”
Section: Discussionmentioning
confidence: 95%